Avaliação de desova induzida hormonalmente e qualidade dos ovos de ariacó, Lutjanus synagris (LINNAEUS, 1758) - Passos Neto, Oscar Pacheco (2010)
The aim of this study was to evaluate the hormone induced spawn and egg quality of lane snapper, Lutjanus synagris. The absolute fecundity, relative fecundity, egg and oil globule diameter, percentage of floating eggs, percentage of fertilization, hatching rate and larval survival up to yolk consumption were assessed. The study was conducted at Centro de Estudos Ambientais Costeiros (CEAC) from Instituto de Ciências do Mar (LABOMAR) from the Universidade Federal do Ceará (UFC). Wild juveniles were captured by hook, took to the laboratory and held in a quarantine system. Fishes were transferred to the internal system to complete gonadal maturation under a 14h-light photoperiod and fed fish, shrimp and squid. After gonadal maturation, induced spawn period was started. Individuals were captured, anesthetized and measured. Maturity criteria were running milt for males and mean oocyte diameter greater than 400 μm for females. Induced spawns were attempted in the period between November 2009 and March 2010, by using human chorionic gonadotropin (hCG) injections at the base of the pectoral fin. Total doses of 1.500 IU kg-1 were used and two experimental protocols were evaluated. In the Protocol 50/50, injections of hCG were given in two doses of 50% of total dose while in the Protocol 70/30, the first dose was 70% and the second was 30% total dose. The second injection was given after 24 hours. Males received only one injection of 750 IU kg-1, at the time of the second injection to females. The sex ratio (female:male) was 1:2. The percentage of floating eggs was significantly different, with mean values of 78.18 ± 39.71% and 33.68 ± 41.02% for Protocols 50/50 and 70/30, respectively. There were no significant differences in any other evaluated parameters. The mean values of relative fecundity were 306,815.10 ± 135,218.18 egg kg-1 (Protocol 50/50) and 404,511.27 ± 261,545.16 egg kg-1 (Protocol 70/30). The percentage of fertilization in floating eggs ranged from 92 to 100% with mean egg diameters from 726.0 ± 16.89 μm to 795.0 ± 19.43 μm and oil globule diameters from 122.5 ± 8.07 μm to 141.5 ± 11.89 μm in Protocols 50/50 and 70/30. Hatching occurred 16 hours after spawning at mean temperature of 29.3 ± 0.9oC. Spawns with eggs having multiple oil globules had a similar hatching rate and larval survival than those with simple oil globule. Lane snapper can successfully adapt to captivity conditions and positively respond to handling and induced spawn. The positive results show that hCG induced spawn is feasible, however the variability of the found data in the present study reveals that this technique needs to be improved